AKIBAT HUKUM PERKAWINAN YANG TIDAK DICATATKAN PADA KANTOR CATATAN SIPIL TERHADAP HARTA BERSAMA - Ginting, Raymond; Sudantra, I Ketut (Kertha Semaya : Journal Ilmu Hukum, 2014)
A marriage is valid when it is carried out according to the consecutive religious and belief laws. In addition, any marriage should be registered according to the prevailing legislation. For the Moslems, recording a marriage conducted in the Civil Registerof Marriages, Divorces and Reconciliation, while while for the non-Islamic religion, marriage records conducted at the Civil RegistryOffice. Nevertheless, there were still many marriage unregistered, the reason being the cost of an expensive marriage records, cumbersome procedures, and people do not know the benefits of marriage records. The legal consequences of unregistered, affect the position of husband and wife, status of childrens and position matrimonial property. A marriage conducted by religion and belief is a legitimate, although unregistered in the office of civil register, it is expressly stipulated in article 2 paragraph 1 of laws number 1 in 1974 about marriage and the practice, in case of divorce in a marriage that unregistered, the position of one party can still claim his rights in court, in this case the division of matrimonial property.
Keywords: Marriage, record, collective property